2010
DOI: 10.1007/s00216-010-3636-5
|View full text |Cite
|
Sign up to set email alerts
|

Beta-keto amphetamines: studies on the metabolism of the designer drug mephedrone and toxicological detection of mephedrone, butylone, and methylone in urine using gas chromatography–mass spectrometry

Abstract: In recent years, a new class of designer drugs has appeared on the drugs of abuse market in many countries, namely, the so-called beta-keto (bk) designer drugs such as mephedrone (bk-4-methylmethamphetamine), butylone (bk-MBDB), and methylone (bk-MDMA). The aim of the present study was to identify the metabolites of mephedrone in rat and human urine using GC-MS techniques and to include mephedrone, butylone, and methylone within the authors' systematic toxicological analysis (STA) procedure. Six phase I metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
161
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(174 citation statements)
references
References 15 publications
13
161
0
Order By: Relevance
“…Meyer et al (2010) suggested the most probable metabolites of mephedrone present in the urine. In this study mephedrone was administered orally and urine was collected over a 24-hour period.…”
Section: Introductionmentioning
confidence: 99%
“…Meyer et al (2010) suggested the most probable metabolites of mephedrone present in the urine. In this study mephedrone was administered orally and urine was collected over a 24-hour period.…”
Section: Introductionmentioning
confidence: 99%
“…It is also a drug of the amphetamine [7] class and a chemical derivative of cathinone that is progressively entering the recreational drug market [8]. It mainly acts as a moderately potent noradrenaline releasing agent, with relatively weak inhibition of dopamine and serotonin reuptake.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the alcohols are conjugated via sulfation or glucuronidation and excreted in the urine [56].…”
Section: Metabolism: Pyrovaleronementioning
confidence: 99%